Pituitary Metastasis of Lung Neuroendocrine Carcinoma Mimicking Pituitary Adenoma:Case Report and Literature Review - Liu, Xiaohai; Wang, Renzhi; Li, Mingchu; Chen, Ge (Frontiers in Endocrinology, 2021)
Pituitary metastasis is an unusual situation in clinical practice, while the incidence is increasing with age. Breast cancer for women and lung cancer for men were the most frequent primary origins of pituitary metastasis. Diagnosing asymptomatic patients with unknown primary malignant origin is difficult, thus pituitary metastasis may be diagnosed as primary pituitary adenoma. Here, we report a case of a 65-year-old patient with visual changes and diabetes insipidus, showing an extensive mass in the sellar region which was initially thought to be a primary pituitary adenoma. Patient corticotropic deficits were corrected, and transnasal transsphenoidal surgery was adopted, leading to total tumor resection. Tumor texture during surgical procedure was similar to that of pituitary adenoma. However, the histopathological and immunohistochemistry results suggested it as a pituitary metastasis from lung neuroendocrine tumor. Postoperative chest CT scan confirmed a pulmonary mass consistent with primary neoplasm. Abdominal CT further detected multiple metastases in liver, pancreas, and colon. Despite intensive treatment, the patient continued to show decreased level of consciousness due to cachexia, resulting in death 1 week after surgery. This case highlights the importance of differential diagnosis of invasive lesions of the sellar region, especially in individuals over 60 years of age with diabetes insipidus.